2019
DOI: 10.1101/853556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Micro-pellet culture reveals that bone marrow mesenchymal stromal cell (BMSC) chondrogenic induction is triggered by a single day of TGF-β1 exposure

Abstract: Despite immense promise, engineering of stable cartilage tissue from bone marrow-derived stromal cells (BMSCs, also known as bone marrow-derived "mesenchymal stem cells") remains elusive. Relative cartilage-like matrix deposition is commonly used to guide BMSC chondrogenic optimisation efforts. However, matrix deposition is heterogeneous in most models, and notably, it lags behind cell fate decisions. We reason that the lag time between cell fate decision and matrix accumulation, coupled with matrix heterogene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
(67 reference statements)
2
12
0
Order By: Relevance
“…The second was the duration of chondrogenic culture (6 weeks in the previous study [23] and 2 weeks in our study). In previous work, we demonstrated that pellets formed from 2 × 10 5 cells each suffer profound gradients and yield heterogenous tissues [25,26]. In large-diameter pellets, differentiation appears to occur first at the peripheral edge of the pellet, with differentiation in the core being delayed, likely due to metabolite limitation in large-diameter tissues.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The second was the duration of chondrogenic culture (6 weeks in the previous study [23] and 2 weeks in our study). In previous work, we demonstrated that pellets formed from 2 × 10 5 cells each suffer profound gradients and yield heterogenous tissues [25,26]. In large-diameter pellets, differentiation appears to occur first at the peripheral edge of the pellet, with differentiation in the core being delayed, likely due to metabolite limitation in large-diameter tissues.…”
Section: Discussionmentioning
confidence: 85%
“…We posit that common large-diameter cartilage tissue models, which suffer large diffusion gradients and tissue heterogeneity, confound efforts to identify optimal BMSC chondrogenic induction protocols. In previous work, we demonstrated that it was possible to obtain more definitive insights into BMSC chondrogenesis, in vitro, if a more homogenous micro-pellet model system was used [24][25][26]36]. In previous studies, it was reported that intermittent and constant PTH treatment of cells could result in profoundly alternate differentiation Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that KGN preconditioning likely improved chondrogenic differentiation of umbilical cord blood-derived mesenchymal stromal cells by committing them to a pre-cartilaginous stage with enhanced JNK phosphorylation and suppressed β-catenin 21 . Our team recently reported that exposing human BMSC to a single day of TGF-β1 yielded differentiation outcomes similar to BMSC exposed to TGF-β1 for 21 days 22 . This observation is specifically relevant to this paper for two reasons: (1) in the human BMSC micropellet model, a single day of TGF-β1 is sufficient to trigger chondrogenic induction, while 14 days of continuous KGN had minimal impact on human BMSC chondrogenesis; and (2) the mechanism by which a single day of TGF-β1 exposure drives BMSC differentiation appears to be fundamentally different than the mechanism by which KGN pre-conditioning of human umbilical cord-derived mesenchymal stromal cells promoted subsequent chondrogenesis in response to TGF-β3 21 .…”
Section: Discussionmentioning
confidence: 98%